Regional expression of the platelet-derived growth factor and its receptors in a primate graft model of vessel wall assembly. - Kraiss, L W (1993)
Healing baboon polytetrafluoroethylene grafts express PDGF mRNA in the neointima. Perfusates of graft segments also contain PDGF-like mitogenic activity. To extend these findings, we studied the expression and regional distribution of the PDGF protein isoforms and their receptors in this prosthetic graft model. By immunohistochemistry, as well as ELISA and Western blot analysis of tissue extracts, both PDGF-A and PDGF-B were identified in macrophages within the interstices of the synthetic material. In contrast, the neointima contained predominantly PDGF-A localized to the endothelial surface and the immediate subjacent smooth muscle cell layers. Tissue extracts of neointima and graft material were mitogenic for baboon aortic smooth muscle cells in culture; nearly all of this proliferative activity was blocked by a neutralizing anti-PDGF antibody. PDGF receptor beta-subunit mRNA and protein were easily detectable in the neointima and graft material. PDGF receptor alpha-subunit mRNA was also observed in the graft matrix and at lower levels in the neointima. This pattern of ligand and receptor expression further implicates locally produced PDGF as a regulator of neointimal smooth muscle cell growth in this model. The coexpression of ligand and receptor in the macrophage-rich matrix also suggests that PDGF may participate in the foreign body response.